2012
DOI: 10.3109/0886022x.2011.647338
|View full text |Cite
|
Sign up to set email alerts
|

Additive Effectiveness of Everolimus Plus Tamoxifen Therapy in Treatment of Encapsulating Peritoneal Sclerosis

Abstract: Peritoneal dialysis (PD) is one of the commonly used choices of continuous renal replacement therapies. Peritoneal membrane is damaged by using solutions with lower biocompatibility, peritonitis episodes, and vintage of PD therapy. Encapsulating peritoneal sclerosis (EPS) is a rare complication of PD and is presented by progressive fibrosis of the peritoneum. Fibrous tissue entrapment of the intestine, leading to complete intestinal obstruction, is referred to as EPS, the most severe form of sclerosing periton… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 16 publications
0
18
0
1
Order By: Relevance
“…Two previous case report suggested favorable use of everolimus for PD patients who developed EPS . However, Temple et al published a report as a letter where a renal transplant patient developed EPS despite the use of sirolimus, i.e., its use did not prevent the subsequent development of EPS …”
Section: Discussionmentioning
confidence: 99%
“…Two previous case report suggested favorable use of everolimus for PD patients who developed EPS . However, Temple et al published a report as a letter where a renal transplant patient developed EPS despite the use of sirolimus, i.e., its use did not prevent the subsequent development of EPS …”
Section: Discussionmentioning
confidence: 99%
“…mTOR inhibitors are well-known for having antiproliferative effects and have recently been used as medical treatment for ESP after transplantation [9]. The synergistic effects of mTOR inhibitor and tamoxifen have also been reported [10]. However, the optimal dose and duration have not been determined.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, effective therapy for peritoneal fibrosis in clinic is scarce [40]. Some cases reported that mTOR inhibitors, with their antifibrotic properties, may be useful in the treatment of encapsulating peritoneal sclerosis (EPS), the most severe form of peritoneal fibrosis [ 41,42]. Recently, the limited studies have shown the effect of rapamycin in preventing the development of peritoneal fibrosis in experimental rat models [22,25].…”
Section: Discussionmentioning
confidence: 99%